Allergic Sensitization, Rhinitis and Tobacco Smoke Exposure in US Adults - Shargorodsky, Josef (PLoS One, 2015)
INTRODUCTION: Tobacco exposure has been linked with sinonasal pathology and may be associated with allergic sensitization. This study evaluates the association between exposure to active smoking or secondhand smoke (SHS) and the prevalence of rhinitis and allergic sensitization in the US adult population. METHODS: Cross-sectional study in 4,339 adults aged 20–85 in the National Health and Nutrition Examination Survey, 2005–2006. Never smoking was defined as reported lifetime smoking less than 100 cigarettes and serum cotinine levels <10ng/ml, while active smoking was defined as self-reported smoking or serum cotinine concentrations > 10 ng/mL. Self-reported rhinitis was based on symptoms during the past 12 months, and allergen sensitization was defined as a positive response to any of the 19 specific IgE antigens tested. RESULTS: Almost half of the population (43%) had detectable levels of IgE specific to at least one inhaled allergen and 32% reported a history of rhinitis. After multivariate adjustment, there was a statistically significant association between the highest serum cotinine tertile and rhinitis in active smokers (OR 1.42; 95%CI 1.00–2.00). The association between active smoking and rhinitis was stronger in individuals without allergic sensitization (OR 2.47; 95%CI 1.44–4.23). There was a statistically significant association between increasing cotinine tertiles and decreased odds of inhaled allergen sensitization (p-trend <.01). CONCLUSION: Tobacco smoke exposure was associated with increased prevalence of rhinitis symptoms, but not with allergic sensitization. The results indicate that the relationship between tobacco smoke exposure and sinonasal pathology in adults may be independent of allergic sensitization.